Triple channel analysis of Gafchromic EBT3 irradiated with clinical carbon-ion beams - Holm, Kim Marina; Yukihara, Eduardo G.; Ahmed, Md Foiez; Greilich, Steffen; Jäkel, Oliver (Physica medica, 2021)
Self-developing radiochromic film is widely used in radiotherapy QA procedures. To compensate for typical film inhomogeneities, the triple channel analysis method is commonly used for photon-irradiated film. We investigated the applicability of this method for GafchromicTMEBT3 (Ashland) film irradiated with a clinically used carbon-ion beam. Calibration curves were taken from EBT3 film specimens irradiated with monoenergetic carbon-ion beams of different doses. Measurements of the lateral field shape and homogeneity were performed in the middle of a passively modulated spread-out Bragg peak and compared to simultaneous characterization by means of a 2D ionization chamber array. Additional measurements to investigate the applicability of EBT3 for quality assurance (QA) measurement in carbon-ion beams were performed. The triple-channel analysis reduced the relative standard deviation of the doses in a uniform carbon ion field by 30% (from 1.9% to 1.3%) and reduced the maximum deviation by almost a factor of 3 (from 28.6% to 9.8%), demonstrating the elimination of film artifacts. The corrected film signal showed considerably improved image quality and quantitative agreement with the ionization chamber data, thus providing a clear rationale for the usage of the triple channel analysis in carbon-beam QA.